2018
DOI: 10.33549/10.33549/physiolres.933704
|View full text |Cite
|
Sign up to set email alerts
|

How To Interpret Elevated Plasmatic Level of High-Sensitive Troponin T in Newborns and Infants?

Abstract: Research and clinical implications on novel cardiac biomarkers has intensified significantly in the past few years. The high-sensitive troponin T (hscTnT) assay plays a dominant role in diagnostic algorithm regarding myocardial injury in adults. Despite generally accepted use of hscTnT there are no data about physiological concentrations and cut-off limits in neonates and infants to date. The aim of this study is to assess hscTnT levels in healthy newborns and infants. Consecutively 454 healthy full termed new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Virtually, all the hs-cTnT values obtained in the present study are considered abnormal in adults based on the latest European guidelines for the reference values, with a cutoff value of >14 ng/L (>99th percentile) [6]. We found that the median hs-cTnT was 39.03 (25th–75th percentiles = 30.53–54.09) ng/L, which is consistent with previous reports [11, 12]. Nevertheless, there are no guidelines related to interpreting troponin values in newborns.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Virtually, all the hs-cTnT values obtained in the present study are considered abnormal in adults based on the latest European guidelines for the reference values, with a cutoff value of >14 ng/L (>99th percentile) [6]. We found that the median hs-cTnT was 39.03 (25th–75th percentiles = 30.53–54.09) ng/L, which is consistent with previous reports [11, 12]. Nevertheless, there are no guidelines related to interpreting troponin values in newborns.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported that cord blood hs-cTnT values were significantly higher in male infants than females [11, 12, 15], which is inconsistent with our result that there were no significant differences between male and female newborns, in the levels of hs-cTnT and with other studies [7, 14, 16, 17, 23, 24]. No significant correlations were found between hs-cTnT and tested laboratory variables including CRP, CK, lactate, pH, pCo 2 , HCO 3, and O 2 saturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited data available on hs-cTnI and hs-TnT circulating levels in pediatric age suggest that biomarker values are greatly increased in the neonates with a successive trend to progressively reduction up to adolescence. 67,82-85 However, hs-cTnI and hs-cTnT values in apparently healthy boys and girls on average tend to remain significantly higher than those measured in adults. 67,82-85…”
Section: Discussionmentioning
confidence: 96%
“…67,82-85 However, hs-cTnI and hs-cTnT values in apparently healthy boys and girls on average tend to remain significantly higher than those measured in adults. 67,82-85…”
Section: Discussionmentioning
confidence: 96%